APPLICATION OF THE SPECTRUM ANALYSIS WITH USING BERG METHOD TO DEVELOPED SPECIAL SOFTWARE TOOLS FOR OPTICAL VIBRATION DIAGNOSTICS SYSTEM - E. O. Zaitsev; V. E. Sydorchuk; A. N. Shpilka (Приборы и методы измерений, 2016)
The objective of this paper is development and experimental verification special software of spectral analysis. Spectral analysis use of controlled vibrations objects. Spectral analysis of vibration based on use maximum-entropy autoregressive method of spectral analysis by the Berg algorithm. For measured signals use preliminary analysis based on regression analysis. This analysis of the signal enables to eliminate uninformative parameters such as – the noise and the trend. For preliminary analysis developed special software tools. Non-contact measurement of mechanical vibrations parameters rotating diffusely-reflecting surfaces used in circumstances where the use of contact sensors difficult or impossible for a number of reasons, including lack of access to the object, the small size of the controlled area controlled portion has a high temperature or is affected by strong electromagnetic fields. For control use offered laser measuring system. This measuring system overcomes the shortcomings interference or Doppler optical measuring systems. Such as measure the large amplitude and inharmonious vibration. On the basis of the proposed methods developed special software tools for use measuring laser system. LabVIEW using for developed special software. Experimental research of the proposed method of vibration signals processing is checked in the analysis of the diagnostic information obtained by measuring the vibration system grinding diamond wheel cold solid tungsten-containing alloy TK8. A result of work special software tools was complex spectrum obtained «purified» from non-informative parameters. Spectrum of the signal corresponding to the vibration process observed object.